USO DE TECNOLOGIAS DA INFORMAÇÃO PARA A APRENDIZAGEM DE MATEMÁTICA FINANCEIRA EM CURSOS TÉCNICOS - Marques, Claiton Regis Timm (2010)
This thesis presents the results of an investigation aiming to analyzing learning contents of financial mathematics in a school in Santa Maria, RS, in a classroom of a technical course of Business Administration and Accounting through contextualized activities, conducted with support from spreadsheets. The first phase of research consisted of a pilot project to adapt the research instruments and the activities planned for students of the technical courses. The instruments employed in the second phase of the research were a questionnaire, observations and analysis of students' productions in the resolution of the proposed activities, undertaken with the spreadsheet. The activities implemented during six meetings are presented in detail, with examples of student responses. The conclusions pointed out the difficulties of working with financial mathematics in technical courses, suggesting a previous preparation, where students have an understanding of the use of spreadsheet and review the content of basic mathematics. To finish the dissertation is presented in Appendix a Manual for use of financial mathematics in technical courses of Business Administration and Accounting.